THE URGENCY OF CHILD EDUCATION MODELS PERSPECTIVE OF TARBAWI HADITS - Muhartini Muhartini; Ilyas Husti; Nurhadi Nurhadi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
Islam places great emphasis on education for every child. Children's education is very urgent, because in childhood a person experiences various kinds of intelligence development. To raise a child well requires a suitable model that has proven itself. There are many models of children's education in the Hadith of the Prophet Muhammad SAW which can be used as a reference for children's education. The purpose of this paper is to examine the models of children's education contained in the hadith and the urgency of their current application. This type of research uses literature studies, based on literature studies it is known that many modern educational models were actually used by the Prophet Muhammad to educate children, including the value explanation technique model, the direct learning model, the inner work model, the learning while playing model. This can be used as a reference in parenting.